Empowerment of aquaculture farmer groups to enhance the productivity of vannamei shrimp (litopenaeus vannamei) through independent feed production training in Padang Sakti Village, Lhokseumawe City [Pemberdayaan kelompok petani tambak untuk meningkatkan produktivitas udang vannamei (litopenaeus vannamei) melalui produksi pakan mandiri di Gampong Padang Sakti, Kota Lhokseumawe] - Eva Ayuzar; Rachmawati Rusydi; Mahdaliana Mahdaliana; K Khairawati; R Rahmaniar; Wahyu Fuadi (Buletin Pengabdian Bulletin of Community Services, 2024)
Padang Sakti Village, located in Muara Satu District and approximately 500 meters from the Malikussaleh University campus, predominantly features traditional aquaculture ponds. Farmers in this village have primarily relied on natural feed sourced from the ponds, although shrimp require pelleted feed for optimal growth. This activity aims to enhance shrimp farming practices through community service, focusing on the cultivation and production of pelleted feed utilizing waste raw materials. The primary objective is to equip shrimp farmers with the knowledge and skills necessary for independent feed production. The methodology employed includes educational, participatory, and persuasive approaches to engage farmers effectively. Analysis of the training outcomes indicates that 90% of participating pond farmers expressed high satisfaction and demonstrated proficiency in ingredient mixing and pellet printing operations. In conclusion, this initiative not only imparts crucial knowledge but also fosters positive motivation among pond farmers, potentially leading to improved productivity in shrimp aquaculture.